Perlindungan Bagi Hak Kekayaan Intelektual Komunal - Putri, Yunita Maya (DE'RECHTSSTAAT, 2021)
Protection of communal intellectual property rights is very important in Indonesia. Because communal intellectual property rights are not based on a "first serve" basis, where the first registrant or innovator is the first to acquire intellectual property. However, this method, because it is not always known when or who invented the concept or created a work for the first time. This research uses empirical normative method by examining regulations and field observations. There are 5 (five) regrets that this Communal Intellectual Property needs to be protected, namely in the context of realizing justice, protection (conservation), preservation (preservation), notification from other unauthorized parties who can carry out piracy (biopiracy) and the use of traditional culture. . The concept of protection of communal intellectual property rights with two models of protection that can be provided through defensive protection and positive protection. Defensive legal protection protection is to prevent other parties from taking over intellectual property rights as well as positive protection that is manifested in the form of legislation.